The impact of alternate methodological and structural assumptions on results of cost-effectiveness analysis: Empirical evidence using three Indian economic evaluations - Deepshikha Sharma; Arun Kumar Aggarwal; Pankaj Bahuguna; Shankar Prinja (Wolters Kluwer Medknow Publications, 2024)
Background: Despite advancement in methods and application of economic evaluations (EEs), there are several uncertainties. Objectives: To assess the impact of alternate methodological and structural assumptions for four key principles of EE, on the results of cost-effectiveness analysis. Materials and Methods: Three previously published model-based EEs were used: (1) Integrated Management of Neonatal and Childhood Illnesses (IMNCIs) intervention; (2) intervention for multiple myeloma, and (3) safety-engineered syringes (SES) intervention. A series of empirical analyses was undertaken to assess the impact of alternate assumptions for discount-rate, time-horizon, study perspective, and health outcome measure, on incremental cost-effectiveness ratio (ICER), and interpretation of cost-effectiveness. Results: Increasing discount rate resulted in an increase in ICERs, for all three case-studies; however, there was no change in the conclusions. Using shorter time-horizons resulted in a significant increase in ICERs, the multiple myeloma intervention remained cost-ineffective, SES intervention became cost-ineffective, whereas IMNCI intervention remained cost-effective, despite a three-fold increase in ICER. On using disability adjusted life years instead of quality adjusted life years, ICERs increased to 0.04, 2 and 4 times for SES, IMNCI and multiple myeloma interventions, respectively. On analyzing results from a societal perspective, a decline in ICERs was observed. The decline was significant for IMNCI where the intervention turned dominant/cost-saving. In the other two case-studies decline in ICERs was modest, 32% for multiple myeloma, and 4% for SES. Conclusion: We observed a significant impact of using alternate assumptions on ICERs which can potentially impact resource-allocation decisions. Our findings provide strong argument in favor of standardization of processes and development of country-specific guidelines for conduct of EE.